Technical Workshop on Gender and Disability-Responsive Disaster Risk Reduction for the IGAD Region - Ackley, Adair G; Shudipta, Aneeshaa C; Jelagat, Joyce (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Disasters disproportionately impact at-risk groups, including women, children, and persons with disabilities, exacerbating existing inequalities. The Sendai Framework for Disaster Risk Reduction (DRR), adopted in 2015, provides a global blueprint to reduce disaster risk and enhance resilience. However, its success depends on ensuring that it is implemented in a way that considers the diverse needs and experiences of all members of society, especially marginalized groups. In November 2024 a training was held on Gender and Disability in Nairobi, Kenya for IGAD Member States: Djibouti, Somalia and Sudan. In April 2025, UNDRR and ICPAC rolled out a similar training for other ICPAC Member States (Burundi, Ethiopia, Kenya, South Sudan, Tanzania, and Uganda). This workshop was co-funded by the CREWS Initiative East Africa project that is being implemented by World Meteorological Organization (WMO), World Bank, and UNDRR. One of the key goals of the project is: Improved integration of gender and vulnerable groups across early warning-early action value chain. The other co-funder of the workshop was the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) programme. AICCRA works to enhance access to, uptake of, and use of climate information services and climate-smart agriculture technologies across Africa.